Predictors of HIV prevention knowledge and sexual behaviors among students at Makerere University Kampala, Uganda - Afra Nuwasiima; Nelson Owuor Onyango; Patricia Navvuga; Elly Nuwamaya; Agnes Nyabigambo; Solomon J. Lubinga; Joseph B. Babigumira (Epidemiology, Biostatistics and Public Health)
Background: Prior reviews argue that unsafe sexual behaviors and poor HIV knowledge significantly increase the probability of acquiring HIV infections among adolescents. This study assessed the predictors of HIV prevention knowledge and sexual behaviors among Makerere university students in Uganda.